2020
DOI: 10.5430/ijhe.v9n3p202
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance, Employment, and Sleep Health: A Comparison between Working and Nonworking Students

Abstract: Interest in overall health and well-being of students in higher education has grown. Retention and success in college has been linked to various health aspects including sleep and alchol usage. The purpose of this study is to: 1) assess sleep health and related behaviors, 2) examine relationships between sleep health and work conditions, and 3) determine if there is a relationship between sleep health and academic performance. Because many students work in service industries due to the flexibility of these job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Evidence from cross-sectional studies indicated that students from lower socio-economic backgrounds [44] and those that perceived themselves in dire financial situations [45] were significantly more likely to report disturbed sleep and poor sleep quality. In addition, research suggests that sleep quality is lower in working students compared to non-working students [45,46]. According to the authors, these factors are in some way linked: Financial needs make it necessary for some students to take on a job while simultaneously attending university, which increases the challenge of balancing work schedules, academic workload, and sleep.…”
Section: The Determinants Of Sleep Quality In University Studentsmentioning
confidence: 99%
“…Evidence from cross-sectional studies indicated that students from lower socio-economic backgrounds [44] and those that perceived themselves in dire financial situations [45] were significantly more likely to report disturbed sleep and poor sleep quality. In addition, research suggests that sleep quality is lower in working students compared to non-working students [45,46]. According to the authors, these factors are in some way linked: Financial needs make it necessary for some students to take on a job while simultaneously attending university, which increases the challenge of balancing work schedules, academic workload, and sleep.…”
Section: The Determinants Of Sleep Quality In University Studentsmentioning
confidence: 99%
“…Covariates were age (continuous), sex (female vs. male) ( 25 ), race (African American/Black, Asian, more than one race, some other race, or White) ( 15 ), ethnicity (Hispanic vs. non-Hispanic/Latinx) ( 15 ), perceived general health (excellent, very good, good, fair/pair) ( 6 8 ), residence type (on-campus/dormitories vs. not on-campus/dormitories) ( 11 , 12 ), year in college (first, second, third, fourth, fifth or more) ( 10 ), total credit hours (≤12 vs. >12), having a job with in-person interaction (no vs. yes) ( 14 ), past 30-day nicotine use (no vs. yes) ( 27 ), alcohol use (no vs. yes) ( 28 ), depressive symptoms (CES-D-10; <10 vs. ≥10) ( 29 31 ), and perceived stress symptoms (PSS-10; continuous) ( 32 ), Additional information about the sociodemographic variables and questions asked in the baseline survey can be found in the Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…Insufficient/short sleep duration is sleeping less than the recommended minimum 7 h for adults and can negatively affect an individual's overall health. Inadequate sleep duration has been linked to diabetes, hypertension, cardiovascular diseases, obesity, depression, and anxiety (6)(7)(8).…”
Section: Introduction Background and Rationalementioning
confidence: 99%
“…For example, if we consider the Portuguese context where the average time spent on academic activities is around 42 h per week (European Commission, 2017) and a full-time worker is required to work at least 35 h per week, we conclude that the time left after a working day to dedicate to study and other activities (e.g., rest) is scarce, compared to the 42 h used by those who do not work. This may justify why studies comparing non-working with working students find more health problems (e.g., anxiety, emotional exhaustion), and worse levels of academic performance and satisfaction for the latter group (e.g., Santana and Salcedo, 2013;Tessema et al, 2014;Chiang et al, 2020). Literature indicates that working students are more susceptible to dropping out due to difficulties in the academic adaptation process (e.g., Hovdhaugen, 2015).…”
mentioning
confidence: 99%